THE INFLUENCE OF PARENT’S EMPTY NEST SYNDROME TOWARDS THE CHILDREN AS REFLECTED ON FAMILY TIES BY DANIELLE STEEL (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2018)
Empty Nest Syndrome is a psychological situation that makes parents experiencing the feeling of loss and sadness when their children leave home. This final project research is conducted in order to investigate the influence of parent’s Empty Nest Syndrome towardsthe children in making decision regarding to them. In fulfilling the objective of this study, the Freudian theory of id, ego, and superego is used to analyze the characters in the novel.The object of this study is the Family Ties novel by Danielle Steel. Content approaching was conducted to collect the data and then they were analyzed using Freud’s psychological approach focused on the psychological conflicts. The results of the research showed that the cause of Empty Nest Syndrome for parent is because of the children’s ids and the effect is the parent’s rejection. This rejection makes the children rebelled the parent’s decisions and its impactis that the children become closer to their parent. Thus, the final conclusion is the Empty Nest Syndrome gives not only bad influences to the person who experienced it but also the good ones, in this case it improves the relationship of Annie and her children.